Phonemic Interpretation of Loan-words from North Germanic Languages in Poli - Awedyk, Sława (Studia Germanica Posnaniensia, 2018)
There are about 30 borrowings from North-German languages in Polish. They are concerned with broad cultural phenomena of these countries. Phonological analysis of loan-words from North-German languages shows that most of them entered Polish in their written form.